Prevalence and factors associated with human Taenia solium taeniosis and cysticercosis in twelve remote villages of Ranomafana rainforest, Madagascar. - Anjanirina Rahantamalala; Rado Lalaina Rakotoarison; Emma Rakotomalala; Mahenintsoa Rakotondrazaka; Jaydon Kiernan; Paul M Castle; Lee Hakami; Koeun Choi; Armand Solofoniaina Rafalimanantsoa; Aina Harimanana; Patricia Wright; Simon Grandjean Lapierre; et al. (Public Library of Science (PLoS), 2022)
Background Infections with the tapeworm Taenia solium (taeniosis and cysticercosis) are Neglected Tropical Diseases (NTD) highly endemic in Madagascar. These infections are however underdiagnosed, underreported and their burden at the community level remains unknown especially in rural remote settings. This study aims at assessing the prevalence of T. solium infections and associated risk factors in twelve remote villages surrounding Ranomafana National Park (RNP), Ifanadiana District, Madagascar. Methodology A community based cross-sectional survey was conducted in June 2016. Stool and serum samples were collected from participants. Tapeworm carriers were identified by stool examination. Taenia species and T. solium genotypes were characterised by PCR and sequencing of the mitochondrial cytochrome c oxidase subunit 1 (cox1) gene. Detection of specific anti-cysticercal antibodies (IgG) or circulating cysticercal antigens was performed by ELISA or EITB/Western blot assays. Principal findings Of the 459 participants with paired stool and blood samples included ten participants from seven distinct villages harbored Taenia spp. eggs in their stools samples DNA sequencing of the cox1 gene revealed a majority of T. solium Asian genotype (9/10) carriage. The overall seroprevalences of anti-cysticercal IgGs detected by ELISA and EITB were quite similar (27.5% and 29.8% respectively). A prevalence rate of 12.4% of circulating cysticercal antigens was observed reflecting cysticercosis with viable cysts. Open defecation (Odds Ratio, OR = 1.5, 95% CI: 1.0-2.3) and promiscuity with households of more than 4 people (OR = 1.9, 95% CI: 1.1-3.1) seem to be the main risk factors associated with anticysticercal antibodies detection. Being over 15 years of age would be a risk factor associated with an active cysticercosis (OR = 1.6, 95% CI: 1.0-2.7). Females (OR = 0.5, 95% CI: 0.3-0.9) and use of river as house water source (OR = 0.3, 95% CI: 0.1-1.5) were less likely to have cysticercosis with viable cysts. Conclusions/significance This study indicates a high exposure of the investigated population to T. solium infections with a high prevalence of cysticercosis with viable cysts. These data can be useful to strengthen public health interventions in these remote settings.